Minerva’s owl is flying at dusk: culture and new civilisation - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2022)
The article considers the role of culture in the process of transition to a new civilisation. The author notes that the stable foundation of the future civilisation is formed in culture, based on the expertise of historical experience, traditions, value preferences, and national characteristics of the peoples living in countries. In conditions of increasing global instability, when it is not clear how to cope with crises, and where are the roots of new challenges and risks, it is essential to identify scenarios that lead to catastrophic consequences in order not to fall into these traps, or at least to see and minimise them. The answer to the new challenges of the time will certainly be found. It has already started forming in the culture, absorbing centuries-old experience of development, traditions and dominant values. The main function of culture is precisely to preserve in memory only that confirms the ideal image of the people. History can constantly return to the same plot in search of acceptable answers for each generation. And here an important feature of cultural identity is considered language as a code and a mechanism for cognition of reality. The building of a new ideal of civilisational development is fixed through the disclosure of a complex developing value system. In such a situation, culture is increasingly associated with the environment of preservation and possible transmission of spiritual civilisational heritage. Now it is impossible to say what a new system of values will be in a new civilisation, it is just emerging.
Keywords: culture; civilisation; historical experience; traditions; values; global instability; crises; the ideal of the new